(3fUjMI GdENhGf heQTOI GdNdGfs - (3GdhQOj GdeUQj GdcfOj, CHh MaU, GHf GdhQOj, Rjf GdOjf, YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, (B749 (3g`s ((3ehQhj MGaX eMeO UGOb Yhfjs)
(3ChdgG (B:s
(3GYJRd PcQ GdCZGfj hGdZRd (B*** (3hbd GdaUd hLGfH ef gRd , hOY GdPcQi dCjGe GdUHG (B*** (3adCjGe GdUHG fLe Cads
(3BNQgG (B:s
(3hbdjd GdeGd ajge jSJad cd Cgd GdYUQ YeQ hCfG efge aGJQc JaGUjd GdMeds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 67s
(3eYLe GdeDdajf(B: 2 / 580s
(3EjVGM Gdecfhf(B: 2 / 52s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs